Toward a Transformative Alchemy: the Phenomenology of the Event of Psychotherapy - Draper, Matthew (Oñati Socio-Legal Series, 2015)
This paper takes up Jung’s concept of Alchemy and applies the theory of this transformational process to prison psychotherapy. In particular, it discusses the manifest meanings in the prison system, how those can be made present and manifest, and how psychotherapy can prove an event, a moment when transformation can take place. It then discusses the openness and closedness of the client and the therapist to the transformational possibilities of the event, and the consequences of those fluid positions. Contextualizing the degree of openness is the adjacent possible in this potentially very human form of relating, and how the apparatus of prisons situated within a broader culture informs the transformational alchemy of forensic psychotherapy.